Building the Local-Based Elements of National Anti Corruption Integrity System in West Sumatera - Valentina, Tengku Rika; Putera, Roni Ekha (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2014)
So far an integrity system was designed by the State, followed by any kind of sanction, when an act of corruption had been committed; thus resulting in a systemic circle of corruption. Reconstructing corruption on the basis of text and theory cannot only be conducted editorially; but must also consider the emergent phenomena. There is something ”missed” by the State, i.e. anti corruption integrity can be initiated from local wisdoms of each region, by employing Model of National Integrity, as suggested by Jeremy Pope, and four indicators of OECD (Organization for Economic Co-operation and Development) as mentioned in Components of Integrity: Data and Benchmarks for Tracking Trends in Government, adopted to generate a local-based model of national anti corruption integrity system on the lowest tier of government in West Sumatera, namely Nagari Kapau of Agam District and Nagari Ketaping of Padang Pariaman District. This research was conducted by employing the method of Grounded Theory. The result of this research shows that inside a Nagari, its apparatus, people and institutions can make join commitment by adopting the virtues of local culture in developing Nagari with integrity principle (anti corruption).